Anisotropy of losses in grain-oriented Fe–Si - E. Ferrara (AIP Publishing LLC, 2021)
Comprehensive assessment of the magnetic behavior of grain-oriented steel (GO) Fe–Si sheets, going beyond the conventional characterization at power frequencies along the rolling direction (RD), can be the source of much needed information for the optimal design of transformers and efficient rotating machines. However, the quasi-monocrystal character of the material is conducive, besides an obviously strong anisotropic response, to a dependence of the measured properties on the sample geometry whenever the field is applied along a direction different from the rolling and the transverse (TD) directions. In this work, we show that the energy losses, measured from 1 to 300 Hz on GO sheets cut along directions ranging from 0° to 90° with respect to RD, can be interpreted in terms of linear composition of the same quantities measured along RD and TD. This feature, which applies to both the DC and AC properties, resides on the sample geometry-independent character of the RD and TD magnetization and on the loss separation principle. This amounts to state that, as substantiated by magneto-optical observations, the very same domain wall mechanisms making the magnetization to evolve in the RD and TD sheets, respectively, independently combine and operate in due proportions in all the other cases. By relying on these concepts, which overcome the limitations inherent to the semi-empirical models of the literature, we can consistently describe the magnetic losses as a function of cutting angle and stacking fashion of GO strips at different peak polarization levels and different frequencies.